Получение поверхностно-барьерных структур на основе четырехкомпонентных твердых растворов А4В6 - Tkachuk, A. I.; Tsarenko, O. N.; Raybets, S. I.; Tkachuk, I. Yu.; Kovalyov, Yu. G. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
Surface‑barrier structures of the type Pb/δ-layer/р-Pb0,87Sn0,13Te0,96Se0,04/р+-Pb0,8Sn0,2Te/Au. were fabricated using liquid‑phase epitaxy and thermal vacuum deposition. At a measurement temperature of 170 K, with a peak wavelength of 8.2 μm and a cutoff wavelength of 8.5 μm, they exhibited a differential resistance–area product at zero bias R0A = 0.39…0.92 Ω·cm², peak quantum efficiency of 0.33…0.42, and specific detectivity of (0.76…1.68)·1010 cm·Hz0.5/W.